Adaptive genetic changes related to haemoglobin concentration in native high‐altitude Tibetans. Issue 11 (1st November 2015) - Simonson, T. S.; Huff, C. D.; Witherspoon, D. J.; Prchal, J. T.; Jorde, L. B.
Abstract : New Findings: What is the topic of this review? Tibetans have genetic adaptations that are hypothesized to underlie the distinct set of traits they exhibit at altitude. What advances does it highlight? Several adaptive signatures in the same genomic regions have been identified among Tibetan populations resident throughout the Qinghai‐Tibetan Plateau. Many highland Tibetans exhibit a haemoglobin concentration within the range expected at sea level, and this trait is associated with putatively adaptive regions harbouring the hypoxia‐inducible factor pathway genes EGLN1, EPAS1 and PPARA . Precise functional variants at adaptive loci and relationships to physiological traits, beyond haemoglobin concentration, are currently being examined in this population. Some native Tibetan, Andean and Ethiopian populations have lived at altitudes ranging from 3000 to >4000 m above sea level for hundreds of generations and exhibit distinct combinations of traits at altitude. It was long hypothesized that genetic factors contribute to adaptive differences in these populations, and recent advances in genomics provide evidence that some of the strongest signatures of positive selection in humans are those identified in Tibetans. Many of the top adaptive genomic regions highlighted thus far harbour genes related to hypoxia sensing and response. Putatively adaptive copies of three hypoxia‐inducible factor pathway genes, EPAS1, EGLN1 and PPARA, are associated with sea‐level range, rather than elevated, haemoglobin concentration observed in many Tibetans at high altitude, and recent studies provide insight into some of the precise adaptive variants, timing of adaptive events and functional roles. While several studies in highland Tibetans have converged on a few hypoxia‐inducible factor pathway genes, additional candidates have been reported in independent studies of Tibetans located throughout the Qinghai‐Tibetan Plateau. Various aspects of adaptive significance have yet to be identified, integrated, and fully explored. Given the rapid technological advances and interdisciplinary efforts in genomics, physiology and molecular biology, careful examination of Tibetans and comparisons with other distinctively adapted highland populations will provide valuable insight into evolutionary processes and models for both basic and clinical research. Abstract :